PERANAN MODAL SOSIAL DALAM PENGELOLAAN PERUSAHAAN AIR MINUM DESA (PAMDES) TRI MANDALA TIRTA (STUDI KASUS: DESA KENDERAN, KECAMATAN TEGALLALANG, KABUPATEN GIANYAR) - Mirayani, Ni Putu (CITIZEN CHARTER, 2014)
ABSTRACT When the government or in this case the Regional Water Company (PDAM) can’t provide the water supply needs, civilizations will fulfill it by themselves. Like people ini Kenderan Village, Tegallanlang Subdistrict, Gianyar, with Village Water Company (PAMDES) Tri Mandala Tirta citizens create and manage water distribution system independently. The purpose of this study was to determine who the village management in utilizing water resources independently. This study used a qualitative exploratory method. By in-depth interview with key informants and field observations researchers got datas needed in this study. The conclusions got from this study is the first, Village Water Company (PAMDES) Tri Mandala Tirta was built from input like public goods and social capital, with management process. Second, in managing the Village Water Company (PAMDES) Tri Mandala Tirta quality and quantity personnels are’t supported but they have a social responsibility to work and build this company. Third, Pupuan villagers and Kenderan villager has embraced the concept of public goods well. Fourth, social capital plays an important role in the existence of this institution, is a network of people who are committed to advancing Kenderan village. Religious norms are believed Kenderan villagers, and trust confidence of the citizens Kenderan Village that committee can development Village Water Company (PAMDES) Tri Mandala Tirta. Fifth, even PDAM Gianyar has been well established but peoples dissatisfaction of PDAM Gianyar service can be a serious threat to the business entity. Keywords: Management, Social Capital, Public Goods